(3beY GdfahS hQbjI GdeCjhSs - (3CHh HcQ Hf eMeO Hf YHO GdeDef Hf nMpQjR Hf eYnqdj GdMSjfj GdMUfj, Jbqj GdOjf,J (B829 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdfGS cGfhG ai LGgdjI LgdkG hYejI YejkG MJi LGA GdMb hRgb GdHGWd Ef GdHGWd cGf RghbkG bGd Gddg JYGdi (B( (3EfG CQSdfGc HGdMb HTjQkG hfPjQG (B) s
(3BNQgG (B:s
(3jfJgi HCKfGA HGH GdLGQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B74s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1356s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs